Status and nutritional therapy in elective and emergency neurosurgery patients - Márcia Maria Teixeira de Freitas; Patrícia Stanich; Solange Diccini
ABSTRACT Objevect: To evaluate the Nutritional Status (NS) and follow the Enteral Nutritional Therapy (ENT) of patients in neurosurgical intervention. Method: Cohort study in emergency or elective surgery patients with exclusive ENT. Anthropometric measurements (Arm Circumference (AC and Triceps Skinfold (TSF)) were measured on the first, seventh and 14th day. For the ENT monitoring, caloric/protein adequacy, fasting, inadvertent output of the enteral probe and residual gastric volume were used. Results: 80 patients, 78.7% in emergency surgery and 21.3% in elective surgery. There was a reduction in AC and Body Mass Index (BMI) (p>0.01), especially for the emergency group. The caloric/protein adequacy was higher in the emergency group (86.7% and 81.8%). Conclusion: The EN change was greater in the emergency group, even with better ENT adequacy. Changes in body composition are frequent in neurosurgical patients, regardless of the type of procedure.